IMPLEMENTASI APLIKASI INTEGRATION REVIT TO ROBOT DALAM ANALISIS STRUKTUR JEMBATAN - Gilang Romadhon; Andi Indianto (Politeknik Negeri Jakarta, 2025)
Structural analysis is currently evolving toward data integration systems, such as those developed with BIM. One such structural analysis tool is Revit Structure and Robot Structural Analysis. To gain recognition in the structural design industry, these new analysis tools must be proven reliable. Therefore, this study compares the reliability of Revit to Robot Integration with SAP 2000 software. The case study used is the Cimake arch bridge in Serang, Banten. The structural analysis used loads in accordance with SNI 1725-2016. The structural analysis results show that Robot Structural Analysis produces results nearly identical to those obtained with SAP 2000, with insignificant differences. The differences in the analysis results indicate variations in several parameters. For axial forces, the difference ranges from 0.00% to 6.67%. For shear forces, the difference ranges from 0.00% to (-1.89)%. In the moment force the difference ranges from 0.00% - (-1.49)%. In the cross-section ratio, it ranges from 0-75)%. In weight, there is no difference, and in deflection, there is a difference of 0.005%. This discussion concludes that the use of Revit to Robot Integration provides a number of benefits, including providing ease of data transfer, information coordination, efficiency, and productivity. However, it should be noted that there are differences in the results of the analysis of the two programs, although the differences are not significant.